COMPARATIVE STUDY BETWEEN JAVA AND C++ PROGRAMMING LANGUAGES - Hj. Hamdan, Nur Liyana (Universiti Teknologi Petronas, 2006)
This Final report represents a proposed project for comparing the use of language features in C++ and Java programming languages. The key idea of this study will contribute to a better accuracy of decision making as well as better understanding of both C++ and Java languages. It also will provide new and more detailed information about the features, design and the implementation of using the respective languages. At the end ofthe project, the thing that I want to accomplish is to be able to help and guide software developers and programmers in the decision making of choosing the best and the most suitable programming languages in developing software or programs and in this case, between the two programming languages, Java and C++ languages.